Implementasi Algoritme Light Encryption Device (LED) pada Wireless Sensor Network dengan Media Pengiriman Data nRF24L01 - Septian Visiano Handoko; Ari Kusyanti; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The nRF24L01 module is more frequently used to send data on Wireless Sensor Network (WSN) compared to the ESP8266 module. This is because of the nRF24L01 module tend to be an Ultra Low Power (ULP) module which requires less power and can transmit data at speeds of 2Mbps. The nRF24L01 module can use 125 different channels and able to create 125 networks in one area and on each channel that has up to 6 addresses. The number of channels and adressess which can be made by the nRF24L01 will make the data traffic will be slightly harder to control and will having a chance to cause a security problem, such as it becomes more vulnerable to hack. Because there is an opportunity for the problem to occur, cryptographic method is needed to encrypt communications on the nRF24L01 module. The Light Encryption Device (LED) algorithm is a development of the Advanced Encryption Standard (AES) algorithm and it is compatible with hardware because this algorithm is a fairly light algorithm if compared to other symmetric block ciphers in its class such as the AES algorithm itself, so that this LED algorithm can implemented in WSN with nRF24L01 module which tend to be Ultra Low Power to fulfill the basic principle of confidentiality security. The implementation of the LED algorithm on the system makes this system resistant to even passive and active attacks. Keywords: Wireless Sensor Network (WSN), nRF24L01, Light Encryption Device (LED)